2021
DOI: 10.7759/cureus.15453
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Causes of Stillbirth in Omdurman Maternity Hospital, Sudan: A Prospective Cross-Sectional Study

Abstract: Background: Stillbirth is an important indicator of the quality of antenatal health services. This study aimed to identify the incidence and causes of stillbirths among Sudanese women. Method: This is a descriptive cross-sectional hospital-based study that was conducted at Omdurman Maternity Hospital during the period from December 1, 2019 to May 30, 2020. The study sample comprised 285 women who presented with stillbirths. Data were collected using a structured questionnaire administered to women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…15 An incidence of 16 per 1000 births was found in the study conducted by Alsammani et al in Sudan. 16 However, a review carried out by Poudel et al 17 found a pooled rate of 25.15 per 1000 births which is comparatively higher than the rate of stillbirth in this review. Moreover, the study conducted by Adjetey et al 18 carried out in Cape Coast, Ghana found the stillbirth rate as high as 58.5 per 1000 deliveries.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…15 An incidence of 16 per 1000 births was found in the study conducted by Alsammani et al in Sudan. 16 However, a review carried out by Poudel et al 17 found a pooled rate of 25.15 per 1000 births which is comparatively higher than the rate of stillbirth in this review. Moreover, the study conducted by Adjetey et al 18 carried out in Cape Coast, Ghana found the stillbirth rate as high as 58.5 per 1000 deliveries.…”
Section: Discussioncontrasting
confidence: 64%
“…23 Likewise, antepartum haemorrhage (APH) was found as the risk factor of stillbirth in 31.4% (Goldenberg et al) 19 , 8.5% (Yeasmin et al) 22 , 30.3% (Tesema et al) 24 and 13.7% (Halim et al) 15 women who had a stillbirth. However, unexplained/unidentified factors were observed in 24.5% women with stillbirths in the study conducted by Yeasmin et al 22 , 21.5% cases in the study by Jamal et al 21 and in 20% cases of stillbirths in the study by Alsamani et al 16 Vaginal delivery was the principal mode of delivery and caesarean section was also found from 5-35%. Similarly, vaginal delivery was observed in 86.2% and 91.2% in the studies conducted by Yeasmin et al 22 and Patel et al 23 respectively.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding fetal outcomes, intrauterine fetal death occurred in a higher portion when compared with that reported at Omdurman Maternity Hospital in Sudan [35], but was lower than in another regional study, in which it was around 20% [35]. Fetal outcomes were not associated with either the antihypertensive drug regimens used or the mother's seizure control situation.…”
Section: Clinical Researchmentioning
confidence: 55%